2004
DOI: 10.2460/ajvr.2004.65.1265
|View full text |Cite
|
Sign up to set email alerts
|

Methicillin resistance of staphylococci isolated from the skin of dogs with pyoderma

Abstract: The latex agglutination assay for the detection of PBP2a expression coupled with the PCR assay for the mecA gene may provide new information about emerging antimicrobial resistance among staphylococcal isolates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
98
2
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(108 citation statements)
references
References 16 publications
(19 reference statements)
7
98
2
1
Order By: Relevance
“…The frequency of MRSP detected in the present study (94.3%) was much higher than those observed in similar studies (Medleau et al, 1986;Kania et al, 2004;Sasaki et al, 2007;Griffeth et al, 2008;Kawakami et al, 2010), which leads to an important concern in Veterinary Medicine in Brazil. Kawakami, et al (2010) also found a high percentage of MRSP isolates (66.5%) derived from dogs with pyoderma through the investigation of the mecA gene.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…The frequency of MRSP detected in the present study (94.3%) was much higher than those observed in similar studies (Medleau et al, 1986;Kania et al, 2004;Sasaki et al, 2007;Griffeth et al, 2008;Kawakami et al, 2010), which leads to an important concern in Veterinary Medicine in Brazil. Kawakami, et al (2010) also found a high percentage of MRSP isolates (66.5%) derived from dogs with pyoderma through the investigation of the mecA gene.…”
Section: Discussioncontrasting
confidence: 54%
“…The Staphylococcus genus is characterized by its easy development of antimicrobial resistance (Guardabassi et al, 2004;Weese and van Duijkeren, 2010 Methicillin-resistant S. aureus (MRSA) and methicillin-resistant S. pseudintermedius (MRSP) are of great concern in veterinary medicine and public health (Weese and van Duijkeren, 2010). In dogs with pyoderma, the occurrence of MRSP may vary between 0 and 66% (Medleau et al, 1986;Kania et al, 2004;Sasaki et al, 2007;Griffeth et al, 2008;Kawakami et al, 2010).…”
mentioning
confidence: 99%
“…The mecA gene sequences found in S. pseudintermedius are essentially identical to those found in methicillin-resistant S. aureus, 14 and penicillin binding protein 2a has been demonstrated by immunologic methods in methicillin-resistant S. pseudintermedius (MRSP). 4,11 It is presumed that expression of mecA in S. pseudintermedius has the same potential to confer broad clinical resistance to all beta-lactam drugs (penicillins, cephalosporins, carbapenems) as it does in S. aureus and other Staphylococcus species; however, this requires further study.…”
Section: Discussionmentioning
confidence: 69%
“…mecA encodes an altered penicillinbinding protein 2a (PBP2a) (FRANK & LOEFFLER, 2012) and confers resistance to all beta-lactam antibiotics, including penicillins, cephalosporins, and carbapenems (KANIA et al, 2004; VAN DUIJKEREN et al, 2011;PRIYANTHAet al, 2016). In addition, methicillin-resistant S. pseudintermedius (MRSP) strains are commonly resistant to several other classes of non-beta-lactam antibiotics, including aminoglycosides, quinolones, macrolides, phenicols, sulfonamides, and tetracyclines (PAPICH, 2012).…”
Section: Introductionmentioning
confidence: 99%